(untitled) (International Journal of Engineering and Computer Science, 2013)
Conceivable applications include amended mobile web access, IP telephony, gaming services, high-definition mobile TV, video conferencing, 3D television and Cloud Computing. A 4G system provides mobile ultra-broadband Internet access, for example to laptops with USB wireless modems, to smartphones, and to other mobile devices.Network system uses the key technology of information gathering, processing and distribution. These systems should be controlled by a server. To enhance the benefits of these networks, we are introducing 4G systems. This paper proposes TD-LTE technology in 4G systemstowardsenhancing the security of 2G and 3G systems.In this paper two 4G candidate systems are commercially deployed: the Mobile WiMAXstandard and the first-release Long Term Evolution (LTE) standard are discussed with TD-LTE Technology